Long-Term Energy Demand Forecasting in Romania : An End-Use Demand Modeling Approach - Malla, Sunil; Timilsina, Govinda R. (World Bank, Washington, DC, 2016)
This study develops an end-use energy demand analysis model for Romania to project energy demand by sector and end-use for 2015-50. The study finds that Romania's energy demand in 2050 would be 34 percent higher than the level in 2013. The industry sector would be the largest final energy-consuming sector, surpassing the residential sector from 2025 onward. The services sector would exhibit the fastest growth of energy consumption in line with the expected structural change from manufacturing to services. Although population in the country is projected to drop by 7 percent in 2050 from the 2013 level, electricity demand would increase by 46 percent over the same period, because of increased household income and the expanded service sector, which is relatively electricity intensive. Still, per capita electricity consumption in Romania will be about half the European Union 28 average. At the end-use level, thermal processes in the industry sector, space heating in the residential and services sectors, and road transportation in the transport sector would be dominant throughout the study period. The study also shows that improvement of energy efficiency in the heating system would be the main channel to cut energy demand in the country.